Race, religion, & Black Lives Matter : essays on a moment and a movement - Cameron, Christopher, 1983-; Sinitiere, Phillip Luke (Black lives and liberation., 2021)
"An examination of religion's place in the Black Lives Matter movement through the lenses of history, politics, and culture"--